Comparative Analysis of the Biomechanical Characteristics After Different Minimally Invasive Surgeries for Cervical Spondylopathy: A Finite Element Analysis - He, Tao; Zhang, Jun; Yu, Tong; Wu, Jiuping; Yuan, Tianyang; Liu, Rui; Yun, Zhihe; Du, Haorui; Qi, Le; An, Junyan; Xue, Wu; Nie, Xinyu; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Minimally invasive surgeries (MIS), including posterior endoscopic cervical foraminotomy (PECF), microsurgical anterior cervical foraminotomy (MACF), anterior transdiscal approaches endoscopic cervical discectomy (ATd-ECD), anterior transcorporeal approaches endoscopic cervical discectomy (ATc-ECD), have obtained positive results for cervical spondylotic radiculopathy. Nonetheless, there is a lack of the comparison among them regarding their biomechanical performance. The study of this study is to investigate the biomechanical changes of operated and adjacent segments after MIS compared to a normal cervical spine. A three-dimensional model of normal cervical vertebrae C3-C7 was established using finite element analysis (FEA). Afterwards, four surgical models (PECF, MACF, ATd- ECD and ATc-ECD), were constructed based on normally model. Identical load conditions were applied to simulate flexion, extension, lateral bending, and axial rotation of cervical spine. We calculated the range of motion (ROM), intradiscal pressure (IDP), annulus fibrosus pressure (AFP), uncovertebral joints contact pressure (CPRESS), and facet joints CPRESS under different motions.For all circumstances, the best analogy to normal cervical spine was ATc-ECD, whereas ATd-ECD significantly increased ROM and joints CPRESS, and decreased IDP in the operated segment. PECF increased more the operated segment ROM than the MACF, but the MACF obtained maximum IDP and AFP. Except for ATc-ECD, the other models increased joints CPRESS of the operated segment. For adjacent segments, ROM, IDP and joints CPRESS showed a downward trend in all models. All models showed good biomechanics stability. Combination biomechanics, safe and conditions of application, PECF and ATc-ECD could be appropriate choices for cervical spondylotic radiculopathy.